PERSEPSI ORANG TUA TENTANG PERKEMBANGAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN (PENELITIAN SURVEI DI TAMAN KANAK-KANAK (TK) WILAYAH GUGUS III KECAMATAN CIBINONG, KABUPATEN BOGOR) - Sabillah, El; Hapidin, Hapidin; Syamsiatin, Eriva (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2021)
This experiment was intended to describeparents perception about early reading development of children 5-6 years old. The sample of this experiment was 100parents at Kindergarten in Gugus III area In The District of Cibinong, Bogor. The technique of getting sample was quota sampling. Data were collected throught questionnaire. The results of the study of parents' perceptions of the development of early reading of children aged 5-6 years by 76% are in the category of